Insulo‐opercular stereoelectroencephalography exploration in children and young adults: Indications, techniques, and safety - Akanksha S. Chilukuri; Emefa Awkwayena; Taylor J. Abel (Epilepsia Open, 2022)
Abstract Objective Sampling the insulo‐opercular region with invasive recordings is crucial given the importance of this region in epileptic networks and a variety of electroclinical presentations. However, implantation of the insulo‐opercular region via stereoelectroencephalography (sEEG) is considered technically challenging given complex vascular and gray matter relationships in this region. We investigated the safety of insulo‐opercular sEEG exploration in children and young adults using standard sEEG approaches: (1) orthogonal insulo‐opercular (including the pseudo‐orthogonal insulo‐opercular approach) and (2) medial‐lateral insular oblique approach. Methods We performed a retrospective cohort study of 30 consecutive patients who underwent 33 sEEG implantations. All patients had drug‐resistant focal epilepsy, were between the ages of 4 and 21, and were operated at one institution between January 2019 and March 2021. Medical records and neuroimaging were reviewed. Hemorrhage, infection, and other complications were considered as outcome variables. Results A total of 519 electrodes were placed. Eighty‐one were placed orthogonally into the temporal operculum, 53 orthogonally into the frontal operculum, and 19 obliquely into the insula. sEEG electrodes localized seizure onset to the insulo‐opercular region in eight patients, leading to a resection three times, an ablation four times, and one peri‐insular hemispherectomy. Of the 519 electrodes placed, none of them exhibited hemorrhage or serious complications. Of the 153 electrodes placed into the insula, none had any permanent deficits or complications and one had minor bleeding due to the electrode breaking. Significance These results demonstrate that the orthogonal (including pseudo‐orthogonal) and medial approaches to sampling the insula are safe.